Immunotherapy for the treatment of breast cancer. (3rd July 2017) - Moreno Ayala, Mariela A.; Gottardo, Maria Florencia; Asad, Antonela S.; Zuccato, Camila; Nicola, Alejandro; Seilicovich, Adriana; Candolfi, Marianela
ABSTRACT: Introduction : Breast cancer is the most common cancer as well as the first cause of death by cancer in women worldwide. Although routine treatment improves the outcome of early stage breast cancer patients, there is no effective therapy for the disseminated disease. Immunotherapy has emerged as a powerful therapeutic strategy for the treatment of many cancers. Although traditionally conceived as a non-immunogenic tumor, breast cancer is now considered a potential target for immunotherapy. Areas covered : In this review, the authors discuss different immunotherapeutic strategies that are currently being tested for the treatment of breast cancer: These strategies include: (i) blockade of immunological checkpoints, (ii) antitumor vaccines, (iii) regulatory T cell blockade, (iv) adoptive T cell transfer therapy, (iv) adoptive immunotherapy with monoclonal antibodies, and (v) combination of immunotherapy with chemotherapy. Expert opinion : A growing body of evidence indicates that immunotherapeutic strategies can benefit a larger cohort of breast cancer patients than hitherto anticipated. Since breast tumors entail multiple mechanisms to impair antitumor immunity, the immunological characterization of individual tumors and the selection of suitable combinations of chemotherapeutic and immunotherapeutic approaches are required to achieve significant clinical benefit in these patients.